Configurations of a cultural scene : young writers and artists in Madrid, 1918-1930 - Anderson, Andrew A., 1953- (McGill-Queen's Iberian and Latin American cultures series, 2023)
"Throughout the 1920s, a remarkable number of young writers and artists lived and worked in Madrid, creating an atmosphere of effervescence and an upsurge in creativity that has rarely been equalled. These young people, acquainting themselves with one another within the span of only a few years, came together to form a tightly-woven network of both personal and artistic relationships. In Configurations of a Cultural Scene Andrew Anderson explores this growing community of artists and writers with a focus on how sites of face-to-face interaction in Madrid fostered creative work and forged young identities. Organizing the locations into places of sociability, learning, and residence, Anderson offers five case studies that exemplify the significance of these three points of intersection: Rafael Barradas and his tertulia at the Café de Oriente; an artists' studio located on the Pasaje de la Alhambra; women art students at the Academia de San Fernando who lodged at the Residencia de Señoritas; the artist and writer Gabriel García Maroto; and the close relationship between artist Maruja Mallo and poet Rafael Alberti. Departing from the conventional approaches to the trajectory of individual careers, Anderson privileges the lived experience of artists and writers in his analysis of a rich cultural scene held together by cooperation, exchange, and interpersonal connections."--